The Influence of Early Childhood Education Teachers' Adaptability on the Implementation of the Independent Curriculum - Yuniar, Pira; SP, Yuli Kurniawati; Diana, Diana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This study aims to analyze the influence of early childhood teachers' adaptability on the implementation of the Merdeka Curriculum in North Konawe Regency, with a focus on the obstacles and opportunities faced by teachers in implementing curriculum changes. The curriculum is designed to improve the quality of education in Indonesia, especially in early childhood education. Teacher adaptability is the key to success in implementing this curriculum. This study uses a mix methods method with a sequential explanatory approach, combining quantitative and qualitative. The sample was taken using cluster random sampling with the Slovin formula, involving 143 early childhood teachers through a Google Form questionnaire. Qualitative data were obtained from in-depth interviews with six teachers from three sub-districts. Quantitative analysis was carried out using simple linear regression, while qualitative analysis used interactive techniques. The results showed that early childhood teachers' adaptability had a significant effect on the success of the Merdeka Curriculum implementation with a significance value of 0.000 <0.05. Several schools have started implementing the curriculum with strategies such as attending training, although not yet fully optimal. The main obstacles faced are limited training and resources, while opportunities arise from government support and the use of technology to improve teacher skills. This study contributes to more effective teacher adaptation strategies for the sustainability of curriculum implementation.